Learning in peer teaching of patient relations and communication skills at the “Anamnesegruppen” Munich – proof-of-concept and lessons learned - Kunisch, Raphael; Zimmermann, Peter; Berges, Natalie; Nitzschke, Malte; Schweiger, Felix; Seidl, Mira; Weidenbusch, Marc (GMS Journal for Medical Education, 2021)
Background: Due to the ban on classroom teaching during the pandem-ic, the Munich “Anamnesegruppen” had to be switched to e-learning at short notice. There were no established concepts for this, which is why digitalization was piloted and evaluated for feasibility. Student “Anamnesegruppen”: “Anamnesegruppen” have existed for over 50 years and are organized as independent student peer teaching. In small groups of medical and psychology students, interviews with patients are conducted once a week during the semester. This is followed by a feedback and discussion round, in which ethical and profes-sional questions are discussed in addition to the patient's medical his-tory. The goal is to train the participants' ability to communicate and reflect. Adaptation to digital methods: The anamnesis seminars have been moved to a virtual group room using video conference. Patients were mainly recruited from the participants' circle of acquaintances. The group size was set at eight people each in four groups and supervised by a pair of student tutors. Confidentiality and data protection declara-tions were obtained in writing. Results: By switching to digital anamnesis groups, all four groups were successfully completed. Both the final supervision of the tutors and the electronic evaluation of the participants yielded positive feedback. Compared to the two previous evaluations of the semesters in classroom sessions, there were no significant differences in the evaluation. Discussion: The continuously good evaluation results, which did not differ between the digital format and the classroom course of the previous semesters, show that an ad hoc conversion to digital teaching is possible. We want to stress the fact that elements reflecting the doctor-patient relationship were successfully preserved. For the similarly structured Balint groups, virtual sessions may also be considered. Further research, especially prospective, is desirable in order to better understand the possibilities of digital teaching in this area.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Anamnesis groups; Balint; Corona; COVID-19; Digital teaching; E-learning; Medical history; Pandemic; Patient interview; Peer-teaching; Relationship medicine; Student teaching